Efek Aloe vera dalam Menurunkan Risiko Penyakit Stroke - Angwen Rial Huga; Anggraeni Janar Wulan; M. Yusran (CV. Jasa Sukses Abadi, 2019)
Stroke is a non communicable disease whose prevalence is increasing in Indonesia. The results of the Riset Kesehatan Dasar (Riskesdas) in 2018 showed that an increase in the prevalence of stroke from 7% (in 2013) to 10.9% with the highest proportion was in East Kalimantan (14.7%) and the lowest proportion was in the Papua region (4.1%). The increased prevalence is related to unhealthy lifestyles. Besides that hypercholesterolemia (high cholesterol levels in the blood) is also a risk factor for stroke which if not handled properly will lead to atherosclerotic plaque formation in blood vessels. This plaque can block the flow of blood that carries oxygen to the brain so that it can cause a stroke. One type of plant in Indonesia that has benefits in lowering cholesterol levels is Aloe vera. There are many ingridients of Aloe vera such as amino acids, salicylic acids, anthraquinons, enzymes, magnesiums, zincs, minerals, vitamins (A, C, E), lignins, saponins, phytosterols, monosaccharides, and polysaccharides (glucomannans and acemannans). Based on several studies, Aloe vera can reduce blood cholesterol levels with saponins, phytosterols, and glucomannans compound that have a direct role in lowering cholesterol levels. Saponin will inhibit the absorption of cholesterol in the gastrointestinal tract and increase its excretion, phytosterols will bind cholesterol and prevent cholesterol from being absorbed by the gastrointestinal tract, whereas glucomannan which is fiber will absorb water and inhibit the process of recycling bile salts so that only a few will return to the liver and more excreted through feces. Reduced blood cholesterol levels due to Aloe vera will have a good effect on atherosclerotic plaque so as to reduce the risk of stroke.